FABRIKASI KEMASAN AKSESORI ARSITEKTURAL UNTUK KELOMPOK PENGRAJIN KAMPUNG AMPERA - Rudy Trisno; Clinton Thedyardi (Jurnal Bakti Masyarakat Indonesia, 2020)
A community engagement activity was aimed at the craftsmen of Kampung Ampera to the UNTAR PKM Team to provide training in the fabrication of architectural accessory packaging supported by an invitation from a fashion designer for the needs of the Soiree event in Tulodong, South Jakarta. This event gives work to craftsmen to make packaging with transparent characters that have never been made by craftsmen before, plus the design is expected to have a high intellectual level and is a delicate work for the upper middle-class target. Acrylic material is used as a fabrication material that is often used in fields and architectural work. The packaging is formed by cutting, laser cutting and bending machines to produce transparent packaging that accentuates the accessories for sale. The experimental method is used by adhering to the process of turning the material into the final result, using an acrylic cutting machine to produce bulk cuts with a high degree of fineness, and heaters for bending. The design sketch was developed through a series of tests on several architectural materials with transparent or translucent characters. Production, detailing, and gluing are carried out by a group of craftsmen producing ready-to-sell packaging that was presented at the Soiree event and received good appreciation. The findings in this study are to improve human resources in Kampung Ampera to change the workings of making gold from manuals to the development of cad technology that is more precise and can be made in bulk, in accordance with the development of the Industrial Revolution 4.0.ABSTRAK:Sebuah kegiatan pengabdian kepada masyarakat ditujukan kepada pengrajin Kampung Ampera kepada Tim PKM UNTAR untuk memberikan pelatihan fabrikasi kemasan aksesori arsitektural didukung oleh undangan dari perancang busana untuk kebutuhan acara Soiree di Tulodong, Jakarta Selatan. Acara ini memberikan pekerjaan kepada pengrajin untuk membuat kemasan dengan karakter transparan yang belum pernah dibuat pengrajin sebelumnya, ditambah lagi rancangan diharapkan memiliki tingkat intelektual tinggi dan merupakan pekerjaan halus untuk target kalangan menengah atas. Material akrilik digunakan sebagai material fabrikasi yang kerap digunakan di bidang dan pekerjaan arsitektural. Kemasan dibentuk dengan mesin potong, laser cutting dan bending sehingga menghasilkan kemasan transparan yang menonjolkan aksesori yang dijual. Metode eksperimental digunakan dengan berpegang pada proses memalih material menjadi hasil akhir, menggunakan mesin potong akrilik untuk menghasilkan potongan massal dengan tingkat kehalusan tinggi, dan pemanas untuk bending. Sketsa rancangan dikembangkan melalui serangkaian tes terhadap beberapa material arsitektural berkarakter transparan atau translusen. Produksi, pendetailan dan pengeleman dilakukan oleh kelompok pengrajin menghasilkan kemasan siap jual yang dipresentasikan pada acara Soiree dan mendapatkan apresiasi baik. Temuan dalam penelitian ini adalah meningkatkan sumber daya manusia di Kampung Ampera untuk merubah cara kerja pembuatan keemasan dari manual ke perkembangan teknologi cad yang lebih presisi dan bisa dibuat secara massal, sesuai dengan perkembangan Revolusi Industri 4.0